Implementation of Effective Sentences in Indonesian Learning at the Faculty of Economics Management Study Program in Lamongan Islamic University - Emalia Nova Sustyorini; Bambang Yulianto; Tengsoe Tjahjono; Heny Subandiyah (Enrichment : Journal of Management, 2021)
This study aims to describe: The implementation of effective sentences in learning Indonesian at the economics faculty of the management study program at the Islamic University of Lamongan. This study uses a qualitative research design. The main object of this research is the implementation of effective sentences in learning Indonesian at the Faculty of Economics, Management Study Program, Lamongan Islamic University. The location of this research at the Islamic University of Lamongan. The data in this study are the implementation of effective sentences in learning Indonesian at the Faculty of Economics, Management Study Program, Lamongan Islamic University. Data collection techniques used are observation, interviews, and recording techniques. The technique used is descriptive analysis technique. The results of the research on the implementation of effective sentences in learning Indonesian at the economics faculty of the management study program at the Islamic University of Lamongan are still found imperfections in the use of effective sentences in learning Indonesian at the student level, especially students of the economics faculty of the management study program at the Islamic University of Lamongan.